The Writing and Rewriting of History: Imperial Women and the Succession in Ming China, 1368–1457. (2nd January 2016) - Soulliere, Ellen
Abstract : Relying primarily on Chinese texts written by official and unofficial historians of the seventeenth and eighteenth centuries, and also on the work of historians of the twentieth and twenty-first centuries, this paper examines the ways in which the legitimate authority of imperial women was constructed, contested and exercised in the succession decisions of 1402, 1424, 1425, 1435, 1449 and 1457. It identifies salient features of the discourse of Chinese historical writing about imperial women in the context of the politics of the court. Through close reading of overlapping texts, including the analysis of linguistic features, it considers the evidence that texts were altered to skew historical narratives in favor of the individuals and groups that emerged in dominant positions in disputes about the succession. It reflects on the "genealogy" of historical texts on how and why the history of events concerning imperial women was written and rewritten. It suggests some general principles for approaching the history of imperial women through texts.